Quad‐band circularly polarized super‐wideband MIMO antenna for wireless applications. Issue 6 (24th February 2022) - Kumar, Amit; Saxena, Gaurav; Kumar, Preetam; Awasthi, Yogendra Kumar; Jain, Priyanka; Singhwal, Sumer Singh; Ranjan, Prashant
Abstract: In this article, a Super‐wideband (2.6–22 GHz) two‐elements multiple‐input‐multiple‐output antenna (MIMO) is presented with a dimension of 49 × 54.5 × 1.6 mm 3 on an FR‐4 substrate. The antenna is also exhibited dual circular polarization (RHCP and LHCP) simultaneously at two separate ports at four frequencies of 5.2, 11.5, 14.66, and 16.75 GHz, which are extensively utilized for WLAN, X, and Ku‐band applications. Four EBG cells of various sizes have been installed across the feed line to maintain the antenna's efficiency and control the specific absorption rate (SAR). The antenna has a minimum isolation of 17 dB (20 dB for the important portion) in Super‐wideband (SWB) and excellent diversity performance. Simulated results of antenna‐like return loss, isolation, and diversity parameters have also been verified experimentally, which are in the acceptable range. Also, the calculated maximum SAR at 10 g is 1.095 W/kg with the head voxel model at 3.5 GHz.